Invasive mucinous adenocarcinoma of the lung in a 19-year-old female. (October 2018) - Narahari, Narendra Kumar; Uppin, Shantveer G; Kapoor, Anu; Stalin, Bala Joseph; Paramjyothi, Gongati K
Lung cancers commonly occur in the sixth to eighth decades of life. They are extremely uncommon in first two decades of life. We describe the clinical, radiological, and pathological findings in a 19-year-old female diagnosed with an invasive mucinous adenocarcinoma that was initially mistaken and treated as tuberculosis. This case is being presented to emphasize inclusion of this entity in the differential diagnosis of multifocal consolidations and nodules that do not resolve or persist after treatment, and also to create awareness of the occurrence of lung cancers in young patients.